Membangun CRM (Customer Relationship Management) Pada Usaha UMKM Bola Ubi di Kota Batam - Golan Hasan; Andrew Andrew; Conny Agustin; Seren Seren; Yuyu Enjelia (Komunitas Dosen Indonesia, 2023)
Sustem of the developing technological advances for various business sectors, namely Micro, Small and Medium Enterprises (MSMEs) its call CRM. MSMEs keep up with technological developments by innovating in order to survive and reinforce the long-term relationships that are fostered between businesses and customers. The aim is to help MSMEs automate sales, marketing, and increase customer attention by providing services through social media to support MSME services better in business development, with the topic of how to build customer relationship management (CRM) in the UMKM Bola Ubi Batam City business. The results that Bolaubi Batam UMKM in building Batam City Customer Relationship Management (CRM) uses 3 stages, namely acquire, enhance, and retain. The CRM system that has been implemented is good and is very suitable for Bolaubi's MSME business in utilizing technology through social media, namely whats app business, Instagram, web, Facebook, web, and grabfood, gofood and shoopee food applications used as a form of business interaction tool and operational system support currently running between UMKM Bolaubi and customers and reaching more new customers. This application is made according to customer needs, so that customers increase with better service, long-term relationships are maintained with customers, it is also a solution in the ease of transactions, information and communication with UKMK Bola Ubi.